2020
DOI: 10.3390/ijms21114133
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sugars in the Regulation of the Level of Endogenous Signaling Molecules during Defense Response of Yellow Lupine to Fusarium oxysporum

Abstract: Soluble sugars such as sucrose, glucose and fructose in plant host cells not only play the role as donors of carbon skeletons, but they may also induce metabolic signals influencing the expression of defense genes. These metabolites function in a complex network with many bioactive molecules, which independently or in dialogue, induce successive defense mechanisms. The aim of this study was to determine the involvement of sucrose and monosaccharides as signaling molecules in the regulation of the levels of phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 85 publications
0
32
0
1
Order By: Relevance
“…For example, the levels of MON were respectively 11 and 61 times higher in infected -Si embryo axes than in +Si embryo axes at 72 and 96 h, respectively. It has become clear that sugar starvation causes a horrendous increase in the sensitivity of embryo axes to pathogenic fungus F. oxysporum , which leads to tissue death, as it was demonstrated by our group in a previous study conducted with the same model system [ 27 ]. We have previously shown that F. oxysporum caused dieback of infected L. luteus L.cv.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, the levels of MON were respectively 11 and 61 times higher in infected -Si embryo axes than in +Si embryo axes at 72 and 96 h, respectively. It has become clear that sugar starvation causes a horrendous increase in the sensitivity of embryo axes to pathogenic fungus F. oxysporum , which leads to tissue death, as it was demonstrated by our group in a previous study conducted with the same model system [ 27 ]. We have previously shown that F. oxysporum caused dieback of infected L. luteus L.cv.…”
Section: Discussionmentioning
confidence: 77%
“…The embryo axes were put, within the next twenty minutes after cotyledon dissection, in groups of four onto Whatman filter papers, which were afterward transferred to sterile glass tubes (diameter 3 cm, height 13.5 cm) containing fourteen milliliters of Heller’s mineral medium [ 29 ]. Eight culture conditions were used: +S, embryo axes cultured in vitro on Heller’s medium supplemented with 60 mM sucrose [ 17 , 27 , 28 , 29 , 30 , 32 , 33 , 34 , 38 ], +G, 120 mM glucose, and +F, 120 mM fructose [ 34 ], and −S, embryo axes cultured in vitro on Heller’s medium without sucrose (−Sn, non-inoculated cultured without sucrose and −Si, inoculated cultured without sucrose). Furthermore, axes before being transferred to glass tubes with Heller’s medium were not inoculated (the control, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction of these signaling patterns can alter gene expression, resulting in specific defense responses against stress. The ability of soluble sugar (sucrose and monosaccharides) to act as a primary molecule in the regulation of phytohormones was recently identified [7]. In addition, studies have also found that sugar-induced signal transduction pathways may interact with hormonal pathways by activating a complex and extensive signal network in plant cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, a series of signaling events are initiated to trigger early cellular responses after pathogens are recognized, such as variations in ion fluxes, salicylic acid (SA), abscisic acid (ABA), jasmonic acid (JA), nitric oxide (NO), and hydrogen peroxide (H 2 O 2 ). These compounds are involved in the regulation of numerous defense genes, while saccharides (glucose and fructose) and sucrose are the key signals in the regulation of these signaling molecules during the protection of host plants from pathogenic fungi [7]. Previous studies suggested that the existence of sucrose permits the plants to develop efficient mechanisms of defense, including those against systemic fungal pathogens, such as Fusarium oxysporum [8][9][10].…”
Section: Introductionmentioning
confidence: 99%